Characterization of soil fungal community associating with suppressive soil to Verticillium yellows disease of Chinese cabbage. Issue 3 (22nd December 2020) - Noguchi, Masako Tsujimoto; Nagase, Haruka; Yamauchi, Norihito; Mimuro, Genki; Sakai, Hiroshi; Furusawa, Akiko; Miki, Shizue; Yoshida, Shigenobu
Abstract: Chinese cabbage yellows is a major economically important disease caused by Verticillium dahliae and V. longisporum in Japan. Although it has existed in Chinese cabbage fields that show suppressiveness against the disease, their mechanisms remain unclear. To uncover soil biological characteristics associated with disease suppressiveness, we performed comparative analyses of bacterial and fungal communities among different field soils showing different disease severities of Chinese cabbage yellows in the Gunma Prefecture in Japan. Bacterial and fungal communities in these soils were analysed using polymerase chain reaction–denaturing gradient gel electrophoresis (PCR–DGGE), which indicated that a specific DGGE band with metrics (Rf value) of approximately 28.9 tended to specifically appear in soils with lower disease severities, whereas the nucleotide sequence analysis revealed that the DGGE band was closely related to the sequences that belonged to the Chaetomiaceae family. The fungal strain S69 corresponding to the DGGE band 28.9 was isolated from disease‐suppressive field soil, and the results of the nucleotide sequence analysis suggested that the strain was closely related to Thielavia terricola, a member of the Chaetomiaceae family. The pot experiments revealed that Chinese cabbage yellows was suppressed by strain S69 propagule treatment into soils infested with V. longisporum . Thus, it is suggested that the fungal strain S69 contributed to the soils' disease suppressiveness.